Electro-chemo-mechanically coupled computational modelling of structural batteries. Issue 4 (19th November 2020) - Carlstedt, David; Runesson, Kenneth; Larsson, Fredrik; Xu, Johanna; Asp, Leif E
Abstract: Structural batteries are multifunctional composites that combine load-bearing capacity with electro-chemical energy storage capability. The laminated architecture is considered in this paper, whereby restriction is made to a so called half-cell in order to focus on the main characteristics and provide a computational tool for future parameter studies. A thermodynamically consistent modelling approach is exploited for the relevant electro-chemo-mechanical system. We consider effects of lithium insertion in the carbon fibres, leading to insertion strains, while assuming transverse isotropy. Further, stress-assisted ionic transport is accounted for in addition to standard diffusion and migration. The relevant space-variational problems that result from time discretisation are established and evaluated in some detail. The proposed model framework is applied to a generic/idealized material representation to demonstrate its functionality and the importance of accounting for the electro-chemo-mechanical coupling effects. As a proof of concept, the numerical studies reveal that it is vital to account for two-way coupling in order to predict the multifunctional (i.e. combined electro-chemo-mechanical) performance of structural batteries.